Development and in vitro evaluation of self-emulsifying drug delivery systems liquisolid lozenges of ibuprofen via design of experiments for solubility enhancement and oral epithelial cell permeation (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Ibuprofen lozenges were developed using liquid self-emulsifying drug delivery systems (L-SEDDS) converted into liquisolid compacts (LSCs) to enhance solubility, dissolution, and buccal drug delivery. L-SEDDS formulated with Tween 60 and Imwitor® 742 produced stable Nano emulsions in simulated salivary fluid. The optimized lozenges, selected using a Box–Behnken design, showed significantly faster dissolution and approximately 3.5-fold higher mucosal permeability than ibuprofen powder. Stability studies demonstrated that the optimized formulations maintained their physicochemical properties, dissolution profile, and mechanical strength for 6 months under ambient and accelerated storage conditions. These findings suggest that L-SEDDS-based liquisolid lozenges are a promising strategy for improving ibuprofen delivery.
Keywords: liquisolid lozenges; L-SEDDS; Tween 60; Imwitor® 742